Analysis of Students’ Mathematical Communication Skills in Review of Self-Efficacy in The Project-Based Learning Model Using Project Assessment - Noor, Hanif Juhar; Masrukan, Masrukan; Dewi, Nuriana Rachmani (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2024)
This study aims to analyze the quality of mathematics learning after applying PjBL with project assessment on students' mathematical communication skills (KKM) and students' KKM in terms of self-efficacy in PjBL learning with project assessment. The type of research is a mix method with a sequential explanatory design. In this study, 6 research subjects were taken based on the level of self-efficacy in students of grade X-8 SMAN 6 Cirebon. The results showed that (1) the PjBL learning model with project assessment improved the quality of mathematics learning for KKM students, and (2) research subjects with high self-efficacy categories are able to meet all KKM indicators, namely stating problems into written mathematical ideas, stating mathematical problems in the form of drawings or mathematical models, presenting written mathematical problem solving in an organized and structured manner, and evaluating mathematical ideas in writing. Subjects with moderate self-efficacy categories were only able to meet the KKM indicators, namely expressing problems into written mathematical ideas and expressing mathematical problems into images or mathematical models. Subjects with a low self-efficacy category were only able to meet the KKM indicators, namely presenting written mathematical problem solving in an organized and structured manner, and evaluating mathematical ideas in writing.